KEMAMPUAN BERNYANYI SISWA DALAM MENYANYIKAN LAGU TRADISIONAL NUSANTARA DI KELAS VIII SMP NEGERI 4 PADANG - Endah Puji Astuti; Erfan Erfan; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2018)
Abstract This article aimed to describe the singing ability of students in traditional songs of the archipelago both individually and in groups VIII-1 SMP N 4 Padang. The type of research was qualitative with descriptive method of analysis. Instrument in this research were the researcher and assisted with observation note book, camera, art and culture module and observation sheet. Techniques of data collection in this research were literature study, observation, interview and documentation. The results showed that: 1) the teacher planned the lesson for the implementation of vocal learning, 2) the students’ abilities about vocal techniques such as body attitude, breathing technique, intonation, articulation, phrasering and expression were still low, 3) inequality of students’ ability both individually and in groupwas the benchmark students ability. The result of singing learning was obtained with varying values. Keywords: Ability, Singing, the Traditional Songs of The Archipelago